Dynamics of Population In Relation to Gross Domestic Product With Reference to North East Region (Ner): Exploring the Impact of Population Growth on Economic Development (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The main objective of the paper is to seek the relation betweenpopulation growth and change of Gross Domestic Product at Factor Cost.Population growth could be beneficial or detrimental to economic growth andeconomic growth could have an impact on population growth. The issue ofpopulation and economic growth is as old as economics itself.  By Malthus (1789), the increase of populationtends to surpass the production growth rate. That unfettered population growthin a country could plunge the economy into acute poverty. But this view hasproven unfounded for developed economies and that they manage to achieve a highlevel of economic growth and thus both population and real gross domesticproduct were able to increase simultaneously. This debate between positive andnegative sides of population growth is ongoing.